Leniency Program as an Innovative Legal Tool for Fighting Cartels within The European Union - Agnieszka Barcik; Piotr Dziwiński (Managerial Economics)
The article focuses on discussing the substance of the institution of leniency which is used against cartel agreements. The study was carried out with regard to the provisions of EU law and Polish law. The paper analyses the factors that determine the effectiveness of the leniency program. Some of the considerations were given to the practical effects of applying the scheme by the European Commission and the Office of Competition and Consumer Protection. The article discusses the issue of the impact of the leniency program on the effectiveness of antitrust proceedings and shows the factors which determine the effective functioning of the program.